Epidemiological analysis of Lassa fever control using novel mathematical modeling and a dual-dosage vaccination approach - Akeem Olarewaju Yunus; Morufu Oyedunsi Olayiwola (BMC Research Notes)
Abstract Lassa fever is a serious health issue in West Africa that requires deeper understanding in order to be effectively controlled. Compared to conventional integer-order methods, this study presents an improved analysis of disease dynamics, including vaccine efficacy, by utilizing fractional-order models and the Laplace Adomian Decomposition methods. This research highlights the critical role of fractional-order dynamics and vaccination impact in understanding Lassa fever transmission and evaluating control strategies. It employs stability and sensitivity analyses, as well as the next-generation matrix method, to assess the basic reproduction number. The study offers novel insights into the importance of expanded vaccination coverage, setting it apart from previous works. The study demonstrated that preventive strategies, particularly double-dose vaccinations, are extremely efficient in controlling Lassa fever and lowering infection rates. It emphasizes the significance of increasing vaccination efforts to safeguard groups that are susceptible. The findings offer important epidemiological insights, boosting efforts to eradicate the disease and improve public health in West Africa and beyond.